Reference-Dependent Utility, Product Variety, and Price Competition - Amaldoss, Wilfred; He, Chuan (Management Science, 2018)
Products such as Nike running shoes, Gillette razors, and Gatorade sports drink serve as the standard against which consumers evaluate other members of the category. Empirical evidence suggests that consumers care about not only the consumption utility derived from a product, but also the gain–loss utility in comparison to the reference product of the category. This paper examines how reference-dependent utility affects price competition in a horizontally differentiated market where consumers’ tastes are diverse. When consumer valuations are low, the reference product is priced lower than a nonreference product. In contrast, when consumer valuations are high, the reference product is priced higher than a nonreference product. Moreover, loss aversion on the price dimension always intensifies competition among low-valuation goods, whereas loss aversion on the taste dimension softens competition among high-valuation goods only if consumer sensitivity to the difference in match quality is above a threshold. We also find that an increase in the diversity of consumers’ tastes reduces equilibrium profits if consumer valuation is low but has the opposite effect if consumer valuation is high. We further explore how an increase in the popularity of the reference product affects price competition. Finally, we assess the robustness of the findings by extending the model in different directions. The online appendix is available at https://doi.org/10.1287/mnsc.2017.2834 . This paper was accepted by Juanjuan Zhang, marketing.